Chronic Pain, Health-Related Quality of Life, Chronic Pain-Related Health Care Utilization and Patient-Provider Communication in the Icelandic Population - Þorbjörg Jónsdóttir 1961- (2014)
Patients with chronic pain are among the most frequent users of health care. Relationships between chronic pain and health-related quality of life (HRQoL), as well as chronic pain and health care utilization, are complex and multifaceted and not all individuals with chronic pain consult health care providers. Chronic pain-related health care utilization as well as patients’ perception of communication with health care providers about their chronic pain can be related to different socio-demographic, economic and pain-related factors. The overall purpose of this thesis was to: 1) contribute to knowledge of the prevalence and characteristics of chronic pain in the general population of Iceland; 2) explore how chronic pain affects daily life and HRQoL; 3) study the relationship between socio-demographic, socioeconomic, pain-related variables, chronic pain-related health care utilization and perceived communication with health care providers. Method: This thesis is based on two interdependent studies. Study I was a methodological study to develop an instrument to measure health care utilization and to translate and evaluate psychometric properties of an instrument to measure patient-provider pain-related communication. The Health Care Utilization questionnaire (HCU) was developed from a collection of questions based on previous research. Questions were then discussed in a focus group of eight individuals with chronic pain and a group of ten health care professionals, specialized in chronic pain were asked for comments and advice. The Modified Patients’ Perceived Involvement in Care Scale (M-PICS) was translated into Icelandic, by the research team, to form the Icelandic Perceived Involvement in Care Scale (I-PICS). The two instruments were evaluated by distributing them two samples of individuals experiencing pain, 1) 300 patients experiencing chronic pain and waiting for specialized treatment for pain in three rehabilitation clinics in Iceland and 2) 175 individuals working physically demanding jobs often associated ...